Mathematical model for burden distribution in blast furnace. (January 2016) - Shi, P.Y.; Zhou, P.; Fu, D.; Zhou, C. Q.
Abstract : Burden distribution in a blast furnace is vital to its smooth running. However, it is difficult to directly measure the burden distribution for an operating blast furnace. Therefore, mathematical models have been applied to guide the charging process to achieve the desired burden distribution. The accuracies of such models depend on the prediction of falling curve, stockline profile formation, and burden descent mode. In this study, a new stockline profile formation model is proposed in which new equations have been developed for the inner and outer repose angle by considering the influence of the burden flow's vertical and horizontal velocity at the apex of the stockline profile. Validation of this new stockline profile formation model is provided through comparison between calculated results and experimental data for stockline profile. A stepped burden descending strategy, in which the burden would descend through a specified distance after each ring charging process, is proposed corresponding to the successive charging process. The influence of the burden descending strategy on the falling point, the final burden profile and radial depth ratio of ore to coke is also analysed. The result shows that the burden descending strategy greatly affects the final burden distribution, especially in the peripheral region.